Measuring and Evaluating the Effectiveness of Active Citizenship Education Programmes to Support Disadvantaged Youth - Liu, Liyuan; Donbavand, Steven; Hoskins, Bryony; Janmaat, Jan Germen; Kavadias, Dimokritos (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This edited volume focuses on measuring and evaluating the effectiveness of diverse formal and informal educational programmes and activities across Europe. This publication contributes to the field by offering more empirical evidence as to the effective ways in which education can reduce social gaps in civic and political engagement. As editors, we prioritised the contributions of early-career researchers and those who have adopted fresh approaches and topics and highlighted helpful strategies to improve social equality and provide a more equitable distribution of learning resources among underprivileged groups. After two years' close collaboration among academic editors, journal editors and authors, this Special Issue has finally been released in 2021 with eight papers. Inter alia, three papers focus on the school's role in developing young people's citizenship competences, such as knowledge, skills, interests and attitudes towards diversity. Two articles explore exclusion/minority groups cases, indicating valuable lessons for developing tailored educational materials and/or activities for hard-to-reach groups. As a unique contribution, two more papers emphasise experimental studies: the paper written by Steven Donbavand and Bryony Hoskins provides a comprehensive and systematic review of all the experimental designs on promoting political participation, whereas the submission written by Sven Ivens and Monika Oberle unpacks some details on how a digital intervention operates and improves to produce satisfying outcomes.